Usefulness of exercise test in the diagnosis of short QT syndrome - Giustetto, Carla; Schimpf, Rainer; Borggrefe, Martin (Europace, 2015)
Aims:Short QT syndrome (SQTS) is a rare arrhythmogenic inherited heart disease. Diagnosis can be challenging in subjects with slightly shortened QT interval at electrocardiogram. In this study we compared the QT interval behaviour during exercise in a cohort of SQTS patients with a control group, to evaluate the usefulness of exercise test in the diagnosis of SQTS. Methods and results: Twenty-one SQTS patients and 20 matched control subjects underwent an exercise test. QT interval was measured at different heart rates (HRs), at rest and during effort. The relation between QT interval and HR was evaluated by linear regression analysis according to the formula: QT = β ×HR + α, where β is the slope of the linear relation, and α is the intercept. Rest and peak exercise HRs were not different in the two groups. Short QT syndrome patients showed lower QT intervals as compared with controls both at rest (276 ± 27 ms vs. 364 ± 25 ms, P < 0.0001) and at peak exercise (228 ± 27 ms vs. 245 ± 26 ms, P = 0.05), with a mean variation from rest to peak effort of 48 ± 14 ms vs. 120 ± 20 ms (P < 0.0001). Regression analysis of QT/HR relationship revealed a less steep slope for SQTS patients compared with the control group, never exceeding the value of −0.90 ms/beat/min (mean value −0.53 ± 0.15 ms/beat/min vs. −1.29 ± 0.30 ms/beat/min, P < 0.0001). Conclusion: Short QT syndrome patients show a reduced adaptation of the QT interval to HR. Exercise test can be a useful tool in the diagnosis of SQTS.